EFEK PASTA GIGI EKSTRAK ETANOLIK TEH SEGAR 2% DAN EPIGALLOCATECHIN GALLATE EKSTRAK TEH 0,1% TERHADAP INDEKS PLAK GIGI: EFFECT OF 2% TEA LEAF ETHANOL EXTRACT AND 1% EPIGALLOCATECHHIN GALLATE TEA LEAF TOOTH PASTE TO DENTAL PLAQUE INDEX - Juni Handajani, (Dentika: Dental Journal, 2009)
Green tea (Camellia sinensis) has been widely known as a healthy beverage for years and the most polyphenol components (catechin) of tea is Epigallocatechin gallate (EGCG). The aim of this study was to evaluate the effectiveness of tea leaf ethanolic extract toothpaste and EGCG toothpaste on dental plaque index. The subjects were 45 girls, 10-12 yeras old, under ethical clearance from Ethic Comittee Medical Faculty of Gadjah Mada University, Yogyakarta Indonesia. The subjecs were divided into 3 groups based on caries status (Group I), gingivitis status (Group II) and healthy status (Group III). Each group consisted of 15 subjects, and divided into 3 sub groups based on toothpaste (tea leaf ethanolic extract toothpaste, EGCG toothpaste, and base material toothpaste as control). The subjects were instructed to brush their teeth during 21 consecutive days in the morning and at night. Clinical evaluation was done by PHP Index. Data were taken before treatment in the 7th, 14th and 21st day. Then, they were analyzed using ANOVA and LSD tests. The results showed that the index of PHP was significant difference in each group after using leaf ethanolic extract toothpaste, EGCG toothpaste, and base material toothpaste. This study suggested that the leaf ethanolic extract toothpaste and EGCG toothpaste could have effected to decrease the PHP Index. As conclusion, the leaf ethanolic extract toothpaste is more effective than the EGCG toothpaste to decrease the PHP Index.